Comparison between intracranial collaterals and cerebral hemodynamics in patients with extracranial carotid stenosis versus combined extra- and intracranial stenosis using transcranial duplex - Sara Hamdy; Hani Mohamed Amin Aref; Ramez Reda; Ahmed ElSadek (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2019)
Abstract Background In acute ischemic stroke, collateral circulation plays an important role in maintaining blood flow to the tissue that is at risk of progressing into ischemia, and in increasing the successful recanalization rate without hemorrhagic transformation. Objectives To compare between collaterals in patients with extracranial carotid stenosis alone and in patients having both extracranial and intracranial carotid stenosis and therefore the difference in prognosis between them. Materials and methods A total of 30 patients of acute ischemic stroke were enrolled. The extracranial part of the carotid artery was assessed with color-coded duplex. Transcranial color-coded duplex was done to assess cerebral hemodynamics and collaterals to differentiate between extracranial significant carotid stenosis alone versus combined extra- and intracranial significant carotid stenosis. Results Out of 15 patients with significant extracranial stenosis, 3 of them obtained reversed flow in the ophthalmic artery and 3 patients of them showed change of flow in the anterior cerebral artery(ACA), whereas the other 15 patients of combined stenosis did not show any reversed blood flow in the same arteries which considered nonsignificant. The residual deficit of patients with extracranial stenosis alone was better when compared to that of the other group. Conclusion Our study concluded that transcranial duplex provides useful information about cerebral reserve and status of collaterals which show nonsignificant difference between two studied groups regarding intracranial collaterals. Furthermore, patients with combined extra- and intracranial stenosis were found to have more deficit and worse prognosis than patients with internal carotid stenosis only.